Ability of fermented soymilk byLactobacillus plantarum 1 in bile acids binding - Yusmarini .; Indrati R.; Utami T.; Marsono Y (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Some lactic acid bacteria (LAB) strains have been isolated from spontaneously fermented soymilk which showing proteolytic activity. These isolated were expected could producing bioactive peptides that could lowering cholesterol content when they used for soymilk fermentation. This research was aimed to determine the proteolytic activity of Lactobacillus plantarum 1 R.1.3.2 and L. plantarum 1 R.11.1.2 comparing with L. acidophilus FNCC 0051 as acontrol. Furthermore soymilk fermented with these isolates were monitored for their ability to bind bile acid and these results were compared with the control of soymilk with no fermentation. Proteolytic activities (U/mL) were measured spectrophotometrically using tyrosin as a standard product, while bile acid binding capacity (µM/100 mg protein) using Total bile Acid Binding Kit. The results show that all isolates use in this study had no different proteolytic activity nor bile acid binding capability to that of control strain. The fermentation process could increased their ability to bind with the bile acid.Key words :fermented soymilk, proteolytic lactic acid bacteria, bile acid binding